Ketimpangan Pendapatan Provinsi di Indonesia Tahun 2012-2016 - Fitri, Annisa (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The object of this research is to analyze the inequality of income betweenprovinces Indonesiarwithbpanel1data1ingthesperiodr2012-2016. This study uses datafrom 34 Provinces and uses two conceptual frameworks with 3 test panel data modelsin selecting the best model. According to the test results show that the best model is theCommon Effect Model (CEM) used in analyzing the factors affecting incomeinequality.The results showed that the variable of GRDP per capita (X1) had a negativeand significant effect, the variable of the population (X2) had a positive effect but notsignificant, and the variable (X3) Total (Capital Expenditure, Expenditure of Goods &Services and Employee Expenditure) had a positive and significant effect on the IncomeInequality in Province Indonesia in 2012-2016.